The value of enhanced ethics checks: Initial experiences with PLOS ONE’s updated Human Subjects Research policy - Hoch, Renee; Chenette, Emily J. (PloS one, 2023)
In March 2023, PLOS ONE updated its Human Subjects Research Policy to require that authors provide ethics approval documentation at initial submission for studies reporting research involving human participants [1]. [...]compliance with PLOS policies is checked at multiple points by journal staff. [...]at this early stage, we do not anticipate that the policy will have a significant effect on the number of papers that PLOS ONE publishes, either, despite the increased desk rejection rate.